Perceived changes and perceived transferability for treating intoxicated women victims of violence among emergency clinicians after an alcohol and other drugs training program. (21st June 2019) - Marshall, Amy; Schultz, Tim; de Crespigny, Charlotte
Abstract: Introduction and Aims: Given the significant overlap between alcohol intoxication and violence against women, it is imperative that emergency clinicians are equipped to care for women presenting with both issues. This research aimed to explore emergency clinicians' perceived changes and ability to apply training, particularly to intoxicated women victims of violence. Design and Methods: Using a pre‐post questionnaire, 74 participants of the Emergency Mental Health Alcohol and Drug program were surveyed about their education/training, awareness and use of guidelines and tools, perceived changes in knowledge, skills and confidence and ability to apply the training. Results: Low levels of previous education/training, awareness and use of best practice tools were reported. Although high rates of change in knowledge and confidence were reported after the program, a minority (38%) felt able to apply this to intoxicated women victims of violence. Working in an emergency department ( P = 0.03) and having higher qualifications ( P < 0.01) were the only significant factors affecting their ability to apply the training. Discussion and Conclusions: The lower rates of perceived ability to apply to intoxicated women victims of violence suggest a deficit in ability to translate knowledge into practice. Higher qualifications affected respondents' ability to apply the training to intoxicated women victims of violence, suggesting that general skills learned regarding translating knowledge into practice rather than specific content may have more impact. This research indicates that clinicians' knowledge and confidence can be positively impacted by targeted education/training, but any future education/training must include knowledge translation skills.